2012
DOI: 10.1111/sjop.12020
|View full text |Cite
|
Sign up to set email alerts
|

Development of sense of coherence during two group interventions

Abstract: Burnout is a serious occupational hazard. This study investigated the possibility to develop an effective salutogenic group intervention among employees suffering from severe burnout symptoms. Participants consisted of employees aged 31 to 59 years working in different public service occupations, such as police officers, tax officers, (and other public service officers), and assigned to three different groups: analytic (N = 25), psychodramatic (N = 24) and controls (N = 28). The intervention comprised 16 separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 20 publications
1
65
0
4
Order By: Relevance
“…No significant change of SOC scores occurred. Although other studies have demonstrated that an increase of SOC scores is possible, this requires intensive interventions focused on empowerment and development of reflection capabilities (Super et al 2015, Kähönen et al 2012, Vastamäki et al 2009). The "Healthy Slotermeer" project probably lacked that high degree of intensiveness.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
“…No significant change of SOC scores occurred. Although other studies have demonstrated that an increase of SOC scores is possible, this requires intensive interventions focused on empowerment and development of reflection capabilities (Super et al 2015, Kähönen et al 2012, Vastamäki et al 2009). The "Healthy Slotermeer" project probably lacked that high degree of intensiveness.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
“…Within an occupational context, Kahonen et al (2012) reported on two group interventions (psychodramatic and analytic) promoting SOC in an occupational healthcare context. The psychodrama method was based on socio and psychodramatic techniques, such as drawing, music, and writing, and muscle relaxation and exercises using the imagination.…”
Section: Clinical and Interventional Implicationsmentioning
confidence: 99%
“…These interventions highlight the factors that develop SOC throughout the lifespan and emphasize the flexibility of the construct and its potential influences (Janik & Kroger, 2007;Kahonen, Naatanen, Tolvanen, & Salmela-Aro, 2012;Pallasch & Hameyer, 2008). The following provides examples of interventions promoting SOC in different contexts.…”
Section: Clinical and Interventional Implicationsmentioning
confidence: 99%
“…These interventions highlight the factors that develop SOC throughout the lifespan and emphasize the flexibility of the construct and its potential influences (Janik & Kroger, 2007;Kahonen, Naatanen, Tolvanen, & Salmela-Aro, 2012;Mayer & Boness, 2011;Pallasch & Hameyer, 2008). The following provides examples of interventions promoting SOC in different contexts.…”
Section: Clinical and Interventional Implicationsmentioning
confidence: 99%